Need to Review the West Seti Dam Design - Thapa, Anand B (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
The proposed 195 meter high concrete faced rockfi l dam (one of the highest of its kind) in West Seti Hydroelectric Project in Nepal will impound 1,500 million cubic meters of water. High CFRD dams were only recently constructed since 1980s. Nepal's Ministry of Energy must constitute a panel of experts of high standing in the fi eld of dam/river engineering to seek their advice on the West Seti Project. Engineering aspects of the project must be reviewed before taking the fi nal decision to implement the project. Similarly, the growing concerns echoed through the media about the sharing of downstream benefi ts and problems of submergence of Nepalese territory resulting from the Laxmanpur barrage, which is a direct extension of the West Seti Project, must also be properly addressed. Key words: West Seti Hydroelectric Project; CFRD dam design; Nepal DOI: 10.3126/hn.v5i0.2484 Hydro Nepal Vol. 5, July 2009 Page:35-36